Development of a watershed information system for a vulnerable basin: the case of Ergene basin - Adiller, A.; Onkal Engin, G. (SPRINGER, 2023)
The increasing stress on water resources in the last few decades poses a risk in terms of water quality and quantity. Eliminating these risks and bringing watersheds to a better level are important targets. These goals can only be achieved through effective watershed management involving stakeholders. This study aims to provide more effective watershed management by establishing a web-based system that can support decision-makers in watershed management and involve stakeholders in the management. The Ergene basin, one of Turkey's most populated basins, has been adversely affected by pollution for nearly five decades. The Ergene Watershed Information System (EWIS) was designed as a system to support decision-makers during the management of the Ergene basin. The Ergene Watershed Information System stores water-related (meteorological, hydrometric, and water quality) historical data and scenario analysis data obtained from modeling tools while preserving data integrity. The system can present these data to users individually or comparatively via its visualization component. The system also has the infrastructure to integrate external data or transfer data to external stakeholders. In addition, there is a warning mechanism that informs users in case the parameter defined in the system is exceeded. Finally, it should also be noted that the watershed information system can easily be adapted to different basins.
Keywords: Data analysis; Decision making; Decision support systems; Watershed management; Environmental Sciences & Ecology